An Integrated Study on Data-Driven Corrosion Prediction and Maintenance Decision-Making for Buried Pipelines - Zhang, Tai; Zhang, Jianchang; Zhang, Ni; Yu, Dan (International Journal of Natural Resources and Environmental Studies, 2025)
This paper addresses the corrosion issues of buried pipelines by constructing a corrosion rate prediction model based on neural network algorithms, integrating multi-source data such as in-situ soil physicochemical parameters. Key input parameters of the model were identified through feature analysis, and the model was trained and validated using historical monitoring data. The results demonstrate that the model effectively captures the nonlinear relationships between multiple factors and corrosion rate with high prediction accuracy, particularly in the low corrosion rate range. Furthermore, the paper systematically reviews pipeline anti-corrosion maintenance decision-making methods based on maintenance timing, strategies, and evaluation metrics, comparing the applicability and limitations of reactive, periodic, and predictive maintenance strategies. It emphasizes that an intelligent maintenance system integrating multidisciplinary approaches such as machine learning, risk assessment, and reliability analysis can achieve closed-loop management of pipeline corrosion protection. This approach enhances the economy, safety, and sustainability of maintenance practices, providing theoretical support and decision-making guidance for the intelligent operation and maintenance of oil and gas station pipelines.